Предмет: Математика,
автор: aisha280
пж помогите решить с пошаговыми действиями
15,87×(-1,09)+(-5,87)×(-1,09)
Ответы
Автор ответа:
0
Ответ:
15,87×(-1,09)+(5,87)×(-1,09)=-1,09×(15,87+(-5,87))=-1,09×10=-10,9
Пошаговое объяснение:
15,87×(-1,09)+(5,87)×(-1,09)=-1,09×(15,87+(-5,87))=-1,09×10=-10,9
Похожие вопросы
Предмет: Информатика,
автор: facop66334
Предмет: Литература,
автор: karolina22112
Предмет: Английский язык,
автор: khdlyydylfl
Предмет: Математика,
автор: Умница115895
Предмет: Алгебра,
автор: Subaru008